A challenging "silent depth" clinical scenario in North Macedonia: Unmasking a rare case of amelanotic melanoma with trapezius muscle invasion and metastatic disease - Peneva, Margarita; Gjorgjeska, Andrijana; Ivanova, Maja; Mircevska Zhogovska, Elizabeta; Aleksovski, Darko; Baneva, Evgenija; Breshkovska, Hristina (Centre for Evaluation in Education and Science (CEON/CEES), 2025)
Introduction: Amelanotic melanoma is a subtype of melanoma that exhibits little or no pigment on visual or histological examination. Approximately 1-8% of all melanomas are amelanotic. It can mimic various benign or malignant melanocytic and non-melanocytic skin tumors, thereby presenting a significant diagnostic challenge. Primary amelanotic melanoma with muscle involvement is an extremely rare entity. A review of the literature revealed no series or case reports. Case Report: We present the case of a 62-yearold female patient with primary amelanotic melanoma infiltrating the trapezius muscle. The tumor was excised together with a clinically positive lymph node on the right side of the neck. Computed tomography (CT) angiography of the lungs, abdomen, and pelvis demonstrated bilateral diffuse nodular changes, a mediastinal pretracheal lymph node, and multiple diffuse liver lesions, consistent with secondary deposits. Molecular pathology revealed positivity for the BRAF V600E2/K/R/D mutation, and the patient began firstline targeted therapy with BRAF/MEK inhibition in accordance with protocols for BRAF-positive metastatic melanoma. Three months later, a follow-up CT scan demonstrated complete remission of the previously observed metastatic changes. Conclusion: Primary amelanotic melanoma with muscle involvement is exceptionally rare, with no published series or case reports identified. This case highlights the importance of early detection and treatment in suspected melanoma and underscores the need to consider melanoma in all clinically unclear cases.
Keywords: amelanotic melanoma; muscle invasion; trapezius muscle; metastatic disease